(untitled) (Asian Journal of Plant Biology, 2013)
Mercury contamination of herbal products is a major source of concern globally. The high cost of instrumental determination of mercury means that a lot of cases of contamination would not be detected. Instrumental method alone is time consuming, costly and need skilled personnel. A recent trend in heavy metal monitoring is to employ biological-base system such as using microbes and their enzyme. The use of these kinds of assays in herbal monitoring has not been reported. In this work, a bromelain-based inhibitive assay was successfully used to determine mercury in digested herbal samples. Three of the twenty samples tested showed positive results for mercury with one of the sample exhibiting mercury at levels higher than the maximum permissibility limit (MPL) as found using the instrument Flow Injection Mercury System or FIMS. The bromelain assay requires little reagents and sample volumes, is rapid and low in cost. The bromelain assay can be part of the system involving the use of biological system together with instrumental method. In this system, the enzyme forms a first screening phase. In the second phase, positive samples are validated suing FIMS. Hence monitoring frequency can be increased and results could be obtained faster.